Median Effective Analgesic Concentration of Ropivacaine in Ultrasound-Guided Interscalene Brachial Plexus Block as a Postoperative Analgesia for Proximal Humerus Fracture: A Prospective Double-Blind Up-Down Concentration-Finding Study - Liu, Yang; Xu, Cheng; Wang, Chengyu; Gu, Fei; Chen, Rui; Lu, Jie (Frontiers in Medicine, 2022)
Background: The innervation of the proximal humerus fracture is complicated and unclear. The use of interscalene nerve block has been effective as postoperative analgesia for patients, but the optimal concentration of usage is unknown. Method: This study was conducted on 30 patients with ASA I or II, who are planning to undergo proximal humerus fracture operation. A dosage of 10mL Ropivacaine was administered for the interscalene brachial plexus block (ISBPB) as determined using the up-and-down sequential method. The initial concentration of Ropivacaine in the first patient to receive ISBPB was 0.3%. After a successful or unsuccessful postoperative analgesia, the concentration of local anesthetic was decreased or increased, respectively, by 0.05% in the next patient. We defined successful postoperative analgesia as a VAS score < 4 at rest, within the initial 8 hours after ISBPB. The analytic techniques of linear, linear-logarithmic, exponential regressions and centered isotonic regression were used to determine the EC50 of Ropivacaine, and the residual standard errors were calculated for the comparison of “goodness of fit” Results: The concentration of Ropivacaine ranged from 0.1% to 0.35%. The EC50 (95% confidence interval) from 4 different statistical approaches (linear, linear-logarithmic, exponential regressions and centered isotonic regression) were 0.222% (0.198%, 0.335%), 0.233% (0.215%, 0.453%), 0.223% (0.202%, 0.436%), and 0.232%, respectively. Among all of the 4 models, the linear regression had the least residual standard error (0.1676). Conclusion: The EC50 from the four statistical models for 10ml Ropivacaine in ultrasound-guided ISBPB for postoperative analgesia was distributed in a narrow range of 0.222%–0.233%.